2004
DOI: 10.1385/bter:101:3:265
|View full text |Cite
|
Sign up to set email alerts
|

Selecting Iodine-Enriched Vegetables and the Residual Effect of Iodate Application to Soil

Abstract: A greenhouse pot experiment was conducted to select vegetables for iodine uptake. The residual effect of iodate fertilization on the growth of and iodine uptake by spinach plants were also investigated. Results showed that the concentrations of iodate in soil had significant effect on the biomass of edible parts of pakchoi and spinach (p<0.01), whereas the concentrations of iodate in soil had no significant effect on that of carrots, water spinach, celery, and onion. Iodine concentrations in edible parts of ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
85
1
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(100 citation statements)
references
References 11 publications
9
85
1
1
Order By: Relevance
“…Dai et al (2004) obtained that when applying iodine at a concentration of 5 mg kg -1 , TF from edible parts of different vegetables increased from 0.1 to 10. The values increased in the following order carrot =onion <celery <spinach outbreak < spinach leaf.…”
Section: Conclusionesmentioning
confidence: 99%
See 1 more Smart Citation
“…Dai et al (2004) obtained that when applying iodine at a concentration of 5 mg kg -1 , TF from edible parts of different vegetables increased from 0.1 to 10. The values increased in the following order carrot =onion <celery <spinach outbreak < spinach leaf.…”
Section: Conclusionesmentioning
confidence: 99%
“…Dai et al (2004) obtuvieron que al aplicar yodo a una concentraci贸n de 5 mg kg -1 el TF de las partes comestibles de diferentes vegetales aument贸 de 0.1 a 10. Los valores se incrementaron en el siguiente orden zanahoria = cebolla < apio < brote de espinaca < hoja de espinaca.…”
Section: (Figura 2)unclassified
“…It needs to be underlined that plant tolerance to selenates (IV) and selenates (VI) strongly depends on the cultivation system, whether hydroponics or in the field, with complex processes of sorption occurring in the latter (R铆os et al 2010, Hawrylak-Nowak et al 2015, Smole艅 et al 2015, 2016a. Also in the case of iodine, carrot is far more tolerant to high doses of this element than other vegetable species, including spinach, pak choi and celery (Dai et al 2004). …”
Section: Biomassmentioning
confidence: 99%
“…Basing on literature data, the direct physiological and biochemical causes of increased NO 2 -accumulation after KI or KIO 3 application cannot be established (Dai et al 2004, Smole艅 et. al 2011a,b, 2014b.…”
Section: The Content Of Nitrates (Iii) Nitrates (V) Chlorides Oxalmentioning
confidence: 99%
“…There were 30 "studies" identified from 10 literature sources [10,[20][21][22][23][24][25][26][27][28] that reported I concentration values after similar experiments, i.e., I concentrations in green shoots after simultaneous root exposures in two or more plant species. There were concentration values for 56 species in these literature sources of which 6 also occurred in the experiments carried out for this analysis.…”
Section: Residual Maximum Likelihood Analysis (Reml)mentioning
confidence: 99%